Efeito do pó de vidro na mitigação da reação álcali-sílica de compósitos cimentícios de alto desempenho - Freitas, Taís Oliveira Gonçalves (Universidade Federal de São Carlos, 2019)
For some years researches has been adressing the replacement of part of the cement used in concrete and mortars with alternative materials such as ground glass powder. This alternative reduces 〖CO〗_2, emissions since it’s used a smaller portion of concrete. In order for this substitution to be considered viable and applicable on the market, several factors and possible problems that this incorporation may result should be examined. One of the problems that can compromise the durability of concrete is the Alkali-Aggregate Reaction. This reaction causes expansion and fissure of concrete elements, by the chemical reaction between the reactive aggregate, alkaline concrete ions and hydroxyl ions, in the presence of moisture. So, this work aims to evaluate the effect of the incorporation of ground glass powder into cementied composites in the Alkali-Aggregate Reaction. Cementious composites were made with CPV cement, active silica, additives, sand with a maximum dimension of 1.2 mm, water (water/cement ratio of 0.18) and incorporation of glass powder in the contents of 0%,10%,20%,30% and 50% in volumetric replacement to cement. Tests were performed to characterize cementitious composites, axial compression resistance, capillarity water absorption, tensile strength by diametric compression, tensile strength in flexion, static elasticity module and dynamic. Expansion tests were performed in mortar bars by the accelerated method in order to evaluate the mitigation of expansions. The results show that the incorporation of glass powder did not interfere in the workability of the mixture in the fresh state, and reduced the air content incorporated into the mixture. There was an improvement in the mechanical and physical properties of cementitious composites from 28 days, such as a decrease in water absorption by capillarity and resistance to axial compression, obtaining the highest value for composite with 30% of glass powder in 129.03 MPa and high elasticity modules, in order of 45 to 50 GPa, characteristics of high performance concrete. Concerning the results found for cementitious composites with incorporation of glass powder, they reached values close to those of the reference material. Already for the specific tests of Alkali-Silica Reaction, it is noted that the contents of 10 and 20% of glass powder incorporation increased expansions in the mortar bars studied and the contents of 30 and 50% decreased to expansions, reaching dimensional variations close to 0%. Therefore, the behavior in the face of the Alkali-Silica Reaction varied according to the glass powder content of the mixtures. It was found that 30 and 50% of incorporation are the optimal substitution levels in relation to the alkali-silica reaction.
Effect of glass powder on the mitigation of alkali-silica reaction of high performance cementitious composites.
Keywords: Compósito cimentício; Pó de vidro; Mitigação; Cement composite; Alkali-silica reaction; Glass powder; Mitigation; Reação álcali-silica; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL